2011
DOI: 10.1007/s10404-011-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation of recirculation zones in a sudden expansion microchannel with a rectangular block structure over a wide Reynolds number range

Abstract: This article involves computational and experimental investigations into the flow of a Newtonian fluid through a sudden expansion microchannel consisting of a rectangular block. The results elucidate that the Reynolds number and aspect ratio has a significant impact on the sequence of vortex growth downstream of the expansion channel. The experimental flow visualization results are found to be in good agreement with the numerical predictions of the local fluid dynamics. The simulation results also draw the Re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Embedding structures within a flow channel has been used to generate passive microvortices —thereby creating highly efficient micromixers, 68 — to form recirculation zones in suddenly expanding microchannels, 69 or to generate cell-free zones for blood plasma isolation. 70 These structures operate on the principle that the flow is disturbed by these structures, leading to the creation of low-pressure zones and microvortices that exert forces on the fluid or cells.…”
Section: Resultsmentioning
confidence: 99%
“…Embedding structures within a flow channel has been used to generate passive microvortices —thereby creating highly efficient micromixers, 68 — to form recirculation zones in suddenly expanding microchannels, 69 or to generate cell-free zones for blood plasma isolation. 70 These structures operate on the principle that the flow is disturbed by these structures, leading to the creation of low-pressure zones and microvortices that exert forces on the fluid or cells.…”
Section: Resultsmentioning
confidence: 99%
“…Passive microvortices are created by channel geometries like sudden expansions in microscale channels [7,12,15,18,19], cylindrical microcavities [35], trapezoidal side chambers [14], microbifurcations [28], embedded obstacles inside the flow channel [21,36,37], two counterflowing liquid streams [9] or at the boundary layer between sheath and center stream [22].…”
Section: Introductionmentioning
confidence: 99%
“…The velocity distribution and streamlines were obtained through the experiments and commercial software FLUENT. Tsai et al [13][14][15] focused on the formation of recirculation zones in a sudden expansion microchannel. They found that Reynolds number and aspect ratio are both influential factors for flow patterns in microchannels.…”
Section: Introductionmentioning
confidence: 99%